Pengaruh Work Attitude, Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan pada Karyawan PT Bank BTN KC Medan - Kristina Manik, Dhea; Harahap, Kartini (Teewan Journal Solutions, 2025)
Employee performance is one aspect that must be considered by the company because if employee performance is not appropriate, it will affect the development and progress of the company. To improve the performance of employees, assessing work attitude, and increasing organizational commitment and job satisfaction of employees is needed. The purpose of this study was to determine the effect of work attitude, organizational commitment and job satisfaction on employee performance at PT Bank BTN KC Medan. The research method used is quantitative with an associative approach, and sampling using probability sampling techniques with simple random sampling and using 60 respondents as samples. The results showed that work attitude variables, organizational commitment and job satisfaction had a positive and significant effect on employee performance and all independent variables simultaneously influenced employee performance at PT Bank BTN KC Medan.